Continuity of physical activity practice from childhood to adolescence is associated with lower neck pain in both sexes and lower back pain in girls - Ciccotti Saraiva, Bruna Thamyres [UNESP]; Pinto, Rafael Z.; Oliveira, Crystian Bitencourt [UNESP]; Zanuto, Edner Fernando [UNESP]; Scarabottolo, Catarina Covolo [UNESP]; Delfino, Leandro Dragueta [UNESP]; Botelho Suetake, Vinicius Yukio [UNESP]; Staquencini Gil, Fernanda Caroline [UNESP]; Destro Christofaro, Diego Giulliano [UNESP] (Ios Press, 2020)
BACKGROUND: The literature on physical activity practice through sports as a protective factor for back pain in adolescents is conflicting. However, few studies have aimed to verify if continuity of the practice of physical activity from childhood to adolescence may be related to lower chances of back pain in adolescents. OBJECTIVES: The objective of this study was to analyze the association between physical activity practice from childhood to adolescence and back pain in adolescents. METHODS: The random sample was composed of 870 adolescents with a mean age of 13.7 +/- 2.0 years. The continuity of physical activity practice was assessed through the continuity of sports practice from childhood to adolescence. Pain in the neck and low back were evaluated through a questionnaire. RESULTS: The prevalence of neck pain and low back pain in boys was 17.5% and in girls was 20.9% for neck pain and 21.9% for low back pain. Physical activity practice during childhood to adolescence was a protective factor for neck pain (OR = 0.57 [CI = 0.35-0.94]) and low back pain (OR = 0.53 [CI = 0.33-0.86]) in girls and neck pain in boys (OR = 0.52 [CI = 0.30-0.90]), even after adjusting for confounding factors. CONCLUSION: Girls with physical activity practice during childhood to adolescence were less likely to develop neck pain and back pain when compared to girls who did not maintain practice of physical activity. Similar results were observed in boys considering neck pain.
Keywords: Physical activity; sports; back pain; musculoskeletal disorders; adolescents